Maqasyid Al-Syariah Analysis of Family Resilience in Long-Distance Marriage in Bua District - Ilyas, Agung Suciati; Nawas, M. Zuhri Abu; Arif, Firman Muhammad; Musyahid, Achmad (LP2M IAIN Palopo, 2025)
This study aims to find out the analysis of Maqasyid Al-Syariah and its implications for family resilience in long-distance marriage in Bua District, Luwu Regency. The approach used is qualitative with three points of view, namely juridical, sociological, and regulatory approaches. Data was collected through observation, documentation, literature studies, and in-depth interviews with 16 resource persons consisting of married couples, community leaders, and religious leaders. The analysis process was carried out by data reduction, data presentation, and conclusion drawing systematically to gain a deep understanding of the social dynamics and Islamic family law in the research area. The results of the study show that couples who undergo long-distance marriages face a number of challenges such as suspicion, miscommunication, unmet spiritual needs, financial pressure, and the potential for infidelity that can lead to divorce. However, many couples are able to maintain domestic harmony by trusting each other, maintaining communication, fulfilling rights and obligations, and fostering patience and sincerity. The analysis of maqāṣid al-syarī'ah reveals that the principles of ḥifẓ al-nafs, ḥifẓ al-'aql, ḥifẓ al-nasl, and ḥifẓ al-māl can still be realized when the couple is able to maintain the spiritual, emotional, and economic balance of the family. Socially and scientifically, this research contributes to the strengthening of the study of Islamic law and family resilience by showing that the values of maqāṣid are adaptive and relevant in responding to contemporary social challenges, including the phenomenon of long-distance marriage.